194k views
4 votes
9g=3(-4+5g) solve for g plzzzzzzzzzzzzz

User Pankaj K
by
5.4k points

2 Answers

6 votes

Let's solve your equation step-by-step.

9g=3(−4+5g)

Step 1: Simplify both sides of the equation.

9g=3(−4+5g)

9g=(3)(−4)+(3)(5g)(Distribute)

9g=−12+15g

9g=15g−12

Step 2: Subtract 15g from both sides.

9g−15g=15g−12−15g

−6g=−12

Step 3: Divide both sides by -6.

−6g /-6=-12/-6

g=2

Answer:

g=2

User Waratuman
by
5.9k points
5 votes

9g = 3(5g - 4)

3g = 5g - 4

3g - 5g = -4

-2g = -4

g = -4/-2 = 4/2

Answer: g = 2

User Lionel T
by
5.6k points